Governing the hearth : law and the family in nineteenth-century America - Grossberg, Michael, 1950- (Studies in legal history., 1988)
Presenting a new framework for understanding the complex but vital relationship between legal history and the family, Michael Grossberg analyzes the formation of legal policies on such issues as common law marriage, adoption, and rights for illegitimate children. He shows how legal changes diminished male authority, increased women's and children's rights, and fixed more clearly the state's responsibilities in family affairs. Grossberg further illustrates why many basic principles of this distinctive and powerful new body of law--antiabortion and maternal biases in child custody--remained in e.